TERHEMPASNYA WIBAWA GURU: SATU KAJIAN KONTRASTIF KARYA SASTRA MASA KINI DAN MASA LALU - Rosida Tiurma Manurung (Fakultas Seni Rupa dan Desain ITB, 2008)
In most of the literatures up to the sixties, we could see how important the role of teachers was. For instance, it was told how a student would rush to take over his teacher's bike and stuff once he saw the teacher came in to the school. We could read from the literatures of the past where teachers had always the authority that they were highly respected by the students. In the stories, we could frequently encounter a student would do the lawn mowing for his teacher's sake. Once a student saw a teacher from a distance, he or she would instantly come towards the teacher and greet. On the contrary, in today's literatures, teachers become the object of fun, intimidation, and even insult. It is terribly ironic. Teachers have lost their authority and credibility. In this particular research, the teacher's authority is compared. The study uses descriptive-comparative analysis. The data have been taken from the literatures of the 60s and the era of 2000s and collected through the literature review and interviews. It is expected that this study would regain the snuffed out authority of the teachers. The authoritative teachers are ultimately required so that they can lead a more effective and quality teaching and learning process. The authority of the teachers should be inserted to today's literatures. It is the obligation of the duty of the man of letters to return the teachers to the higher respected human beings. Key words: Teachers' authority, the literature of the 60s and 2000s, comparative analysis